The economic history of Central, East and South-East Europe : 1800 to the present - Morys, Matthias (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The collapse of communism in Central, East and South-East Europe (CESEE) led to great hopes for the region and for Europe. A quarter of a century on, the picture is mixed: in many CESEE countries, the transformation process is incomplete, and the economic catch-up has taken longer than anticipated. The current situation has highlighted the need for a better understanding of the long-term political and economic implications of the Central, East and South-East European historical experience. This thematically organised text offers a clear and comprehensive guide to the economic history of CESEE from 1800 to the present day. Bringing together authors from both East and West, the book also draws on the cutting-edge research of a new generation of scholars from the CESEE region. Presenting a thoroughly modern overview of the history of the region, the text will be invaluable to students of economic history and CESEE area studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Europe, Eastern -- Economic conditions; Europe, Central -- Economic conditions; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General